Visual cortex combines a stimulus and an error-like signal with a proportion that is dependent on time, space, and stimulus contrast - Eriksson, David; Wunderle, Thomas; Schmidt, Kerstin E. (Frontiers in Systems Neuroscience, 2012)
Even though the primary visual cortex is one of the most studied brain areas, the neuronal code in this area is still not fully understood. In the literature, two commonly hypothesized codes are stimulus and predictive (error) codes. Here, we examined whether and how these two codes can coexist in a neuron. We assumed that neurons could predict a constant stimulus, since this is the easiest and most fundamental type of prediction. Prediction was examined in time using electrophysiology in the supragranular layers in the anesthetized cat, and in space using a computer model. We show that the single neuron combines stimulus and error-like coding with a proportion that is changing as a function of time, space and stimulus contrast. The combination of stimulus and error leads to a suboptimal free energy in a recent predictive coding model. We therefore suggest a straightforward modification that can be applied to the free energy model and other predictive coding models. Combining stimulus and error might be advantageous because the stimulus code enables a direct stimulus recognition that is free of assumptions whereas the error code enables an experience dependent inference of ambiguous and non-salient stimuli.